Estimating the Life Expectancy at Birth for Iranian Provinces during 2011-16 - Mohammad Sasanipour (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Life expectancy at birth is a useful indicator of mortality across a population at a particular point in time. Due to the incomplete and different coverage of mortality data in the provinces of Iran, constructing a life table without data correction can have misleading results. In this study, after evaluating and correcting the mortality data, life expectancy at the national and provincial levels for the period 2011-16 has been estimated. Methods: This was a cross-sectional study. Regarding the period 2011 to 2016, mortality data were obtained by age and sex (2051602 deaths) from the National Organization for Civil Registration, and the population data were obtained by age and sex from the Statistics Center of Iran. After evaluating and correcting the mortality data regarding children and adults, through the life table technique, life expectancy at birth for the provinces Iran was calculated by sex. Results: The death registration regarding men and women, during 2011-2016, in the national level was 93% and 85% respectively. Moreover, the range of this coverage for the provinces has been between 70% and 98%. The life expectancy at birth for men was 73.1, and for women it was 76 years. Isfahan (77.9 for females and 74.8 for males) had the highest level of life expectancy at birth, and the lowest level was in Sistan and Baluchestan province (70.4 for females and 69.2 for males). Conclusion: Considering that there are important differences between the life expectancy of men and women in the provinces of Iran, identifying the causes of provincial differences in regarding life expectancy in the provinces of Iran can ultimately lead to improved life expectancy at the national level.